Early costs and complications of first-line low-grade glioma treatment using a large national database: Limitations and future perspectives - Tuohy, Kyle; Ba, Djibril M.; Bhanja, Debarati; Leslie, Douglas; Liu, Guodong; Mansouri, Alireza (Frontiers in Surgery, 2023)
Introduction: Diffuse Low-grade gliomas (DLGG, WHO Grade II) are a heterogenous group of tumors comprising 13-16% of glial tumors. While maximal safe resection is endorsed as the best approach to DLGG, compared to more conservative interventions like stereotactic biopsy, the added costs and risks have not been systematically evaluated. The purpose of this study was to better understand the complication rates and costs associated with each intervention. Methods: A retrospective cohort study using data from the IBM Watson Health MarketScan® Commercial Claims and Encounters database was conducted, using the International Classification of Diseases, Ninth Revision (ICD‐9) codes corresponding to DLGG (2005-2014). Current Procedure Terminology, 4th Edition (CPT-4) codes were used to differentiate resection and biopsy cohorts. Inverse weighting by the propensity score was used to balance baseline potential confounders (age, sex, pre-op seizure, geographic region, year, Charleston Comorbidity Index). Complication rates, hospital mortality, readmission, and costs were compared between groups. Results: We identified 5,784 and 3,636 patients undergoing resection and biopsy, respectively, for initial DLGG management. Resection was associated with greater 30-day complications (29.17% vs 26.34%; p<0.05). However, this association became non-significant after inverse propensity weighting (adjusted odds ratio=1.09; 0.98-1.20). There was no statistically significant difference in unadjusted, 30-day hospital mortality (p=0.06) or re-admission (p=0.52). Resection was associated with higher 90-day total costs (p<0.0001) and drug costs (p<0.0001). Biopsy was associated with greater index procedure costs (p<0.0001). Long-term outcomes and evaluation of DLGG subtypes was not possible given limitations in the metrics recorded in MarketScan and lack of specificity in the ICD coding system. Conclusion: Resection was not associated with an increase in the adjusted complication rate after balancing for baseline prognostic factors. Total costs and drug costs were higher with resection of DLGG, but the index procedure costs were higher for biopsy. This data should help to facilitate prospective health economic analyses in the future to understand the cost-effectiveness, and impact on quality of life, for DLGG interventions. However, the use of large national databases for studying long-term outcomes in DLGG management should be discouraged until there is greater specificity in the ICD coding system for DLGG subtypes.